2017
DOI: 10.1016/j.sjbs.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of arbuscular mycorrhizal fungi in mitigating salt-induced adverse effects in sweet basil (Ocimum basilicum L.)

Abstract: Salinity is one of the serious abiotic stresses adversely affecting the majority of arable lands worldwide, limiting the crop productivity of most of the economically important crops. Sweet basil () plants were grown in a non-saline soil (EC = 0.64 dS m), in low saline soil (EC = 5 dS m), and in a high saline soil (EC = 10 dS m). There were differences between arbuscular mycorrhizal () colonized plants (+AMF) and non-colonized plants (-AMF). Mycorrhiza mitigated the reduction of K, P and Ca uptake due to salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
82
2
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 62 publications
13
82
2
3
Order By: Relevance
“…Other authors also observed significant reduction in basil dry matter in response to salt stress (Zahedi et al, 2011;Fatemi & Aboutalebi, 2012;Heidari, 2012;Bione et al, 2014;Elhindi et al, 2016). In a study conducted by Bione et al (2014) in hydroponic system (NFT), the authors observed reduction in TDM of 6.02% per unit increase in salinity, a value lower than that obtained in the present study.…”
Section: Resultscontrasting
confidence: 62%
“…Other authors also observed significant reduction in basil dry matter in response to salt stress (Zahedi et al, 2011;Fatemi & Aboutalebi, 2012;Heidari, 2012;Bione et al, 2014;Elhindi et al, 2016). In a study conducted by Bione et al (2014) in hydroponic system (NFT), the authors observed reduction in TDM of 6.02% per unit increase in salinity, a value lower than that obtained in the present study.…”
Section: Resultscontrasting
confidence: 62%
“…The development of salt-tolerant crops or desaliniation of soil by leaching excessive salts is not sufficient to overcome this problem. In recent years, the use of the biological applications; mycorrhizal symbiosis as a practical method to alleviate a soil stresses like salinity on plant growth and production has received a greater attention (Elhindi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, little information is available about the relationships of low electric conductivity and magnesium concentrations on the AMF spore density. Most studies on this topic have been conducted to test the impact of the growth of plants in saline soils with AMF inoculation (Elhindi, El‐Din, & Elgorban, ; Pollastri et al., ). As far as we know, our study is the first to suggest that a decrease in electric conductivity and magnesium concentrations might be associated with a low AMF spore density.…”
Section: Resultsmentioning
confidence: 99%